Open Access Policy and Funding in Cyprus University of Technology a Case Study - Zervas, Marios; Artemi, Petros; Giannoulakis, Stamatios (My University, 2017)
Today an increasing number of researchers and scientists follow Open Access. Open Access is a movement that offers researchers and the academic community the opportunity to share and access academic information freely and immediately. The Library and Information Services at the Cyprus University of Technology (CUT) has defined Open Access as one of its main strategies. An author fund has been established since 2013, with the financial support of a pharmaceutical company, in order to promote and support Open Access. Statistics of this Fund have shown that funding covers publications mainly in health sciences. These findings have allowed us to implement a new policy for the financing of Open Access publications from our university’s budget, which falls within the framework of its social responsibility. However, considering the “hybrid model” and the “double dipping” which favors ‘big’ publishers, we will examine the different possibilities and present our reflections and decision for the new policy. Finally we will describe the policy implemented.
Keywords: Author fund policies; Hybrid model; Open Access; Author fund